Islamic fasting and diabetes - Fereidoun Azizi (Journal of Fasting and Health, 2013)
The aim of this article is to review health-related aspects of Ramadan fasting in normal individuals and diabetics. During fasting days of Ramadan, glucose homeostasis is maintained by meal taken bepore dawn and by liver glycogen stores. Changes in serum lipids are variable and defend on the quality and quantity of food consumption and changes in weight. Compliant, well controlled type 2 diabetics may observe Ramadan fasting; but fasting is not recommended for type 1, non complaint, poorly controlled and pregnant diabetics. Although Ramadan fasting is safe for all healthy individuals and well controlled diabetics, those with uncontrolled diabetics and diabetics with complications should consult physicians and follow scientific recommendations.